Antagonistic natural and sexual selection on wing shape in a scrambling damselfly. (1st July 2016) - Outomuro, David; Söderquist, Linus; Nilsson‐Örtman, Viktor; Cortázar‐Chinarro, María; Lundgren, Cecilia; Johansson, Frank
Abstract: Wings are a key trait underlying the evolutionary success of birds, bats, and insects. For over a century, researchers have studied the form and function of wings to understand the determinants of flight performance. However, to understand the evolution of flight, we must comprehend not only how morphology affects performance, but also how morphology and performance affect fitness. Natural and sexual selection can either reinforce or oppose each other, but their role in flight evolution remains poorly understood. Here, we show that wing shape is under antagonistic selection with regard to sexual and natural selection in a scrambling damselfly. In a field setting, natural selection (survival) favored individuals with long and slender forewings and short and broad hindwings. In contrast, sexual selection (mating success) favored individuals with short and broad forewings and narrow‐based hindwings. Both types of selection favored individuals of intermediate size. These results suggest that individuals face a trade‐off between flight energetics and maneuverability and demonstrate how natural and sexual selection can operate in similar directions for some wing traits, that is, wing size, but antagonistically for others, that is, wing shape. Furthermore, they highlight the need to study flight evolution within the context of species' mating systems and mating behaviors.